KETAHANAN TIGA JENIS KAYU UNTUK BANTALAN REL KERETA API TERHADAP JAMUR PERUSAK KAYU SECARA LABORATORIS - Djarwanto Djarwanto; Sihati Suprapti (Jurnal Penelitian Hasil Hutan, 2004)
Wood still performs as the main materials for  railway sleepers, especially at their connected portions,  cross and bridge.  So far, wood has not yet been effectively substituded by other materials. However,  wood based railway sleepers are susceptible to deterioration by the decaying fungi.  This study examined,  the decay resistance of three wood species i.e.  bangkirai (Shorea laevis),  meranti batu  (Shorea  platyclados)  and rasamala  (Altingia exelsa).  Samples  were  evaluated  against  the decayingfungi  in a laboratory experiment using DIN 52176-modified standard.Results  indicated that bangkirai and meranti batu were classified  resistance against fungalattacks (Class II), whereas, rasamala was categorized moderately resistant (Class III).  The weight loss percentage  of rasamala was higher than those of bangkirai and meranti batu.   The ability of fungus  to degrade certain wood was depended upon kinds of wood and fungus  itself. Fungi with significant decay ability were Pycnoporus sanguineus HHB-324, Schizophyllum commune, Polyporus sp.,  Trametes sp. and Tyromyces palustris.The highest  weight losses were recorded on  samples exposed  consecutively  to Pycnoporussanguineus and Schizophyllum commune.